Passage to India: Abhishiktānanda and the Retrieval of the Supernatural in Roman Catholicism - Pedersen, Kusumita Priscilla (Nidān, 2022)
Henri Le Saux, later known as Swami Abhishiktananda (1910-1973), was a French Benedictine monk who went to India at age thirty-eight and lived there for the rest of his life, never returning to France. While remaining a Christian, he immersed himself in Hindu teachings and practices. Much has been written about his spiritual quest and his ideas on the relation of Catholicism and the form of Hinduism to which he was most connected, non-dualist or Advaita Vedanta. Interpretations have varied widely. In this finely nuanced and deeply researched study, Enrico Beltramini seeks to remedy a misleading lack in previous discussions of Abhishiktananda. He finds that writing about Abhishiktananda since his passing almost fifty years ago has gone through three phases: first, a focus on his identity as a spiritual seeker and mystic in works often written by those who knew him; second, a perception of him as a pioneer in interreligious dialogue; and third and more recently, scrutiny of his thought to assess its theological orthodoxy (Beltramini 2018). Overall, Beltramini says, the first part of Abhishiktananda's life has been neglected, making the point that "Abhishiktānanda matured his existential preoccupation in France and …his intellectual interests and theological concerns mainly depend on this preoccupation" (12). This preoccupation was "the retrieval of the supernatural" or the recovery of a "sacramental ontology" - this was his "guiding theological intuition" which provides coherence to his thought and is a key to understanding him. As well, Beltramini states that Abhishiktananda should not be viewed as a theologian, but as a literary artist with theological interests, and that his contributions are best evaluated in this perspective.